Effectiveness of a cognitive behavioral group therapy program for reducing violence risk in persons with schizophrenia - Putri Karlinda; Teguh Pribadi; Sulastri Sulastri (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2020)
Background: Violent behavior is the dominant sign and symptom in patients with schizophrenia. Proper nursing care can help patients independently control violent behavior. A cognitive behavioral group therapy program in stimulation of perception to identify their experience of violent behavior.Purpose: Knowing the effectiveness of a cognitive behavioral group therapy program for reducing violence risk in persons with schizophreniaMethods: A quantitative research by design an experimental analytic with pre and post-experiment approach. The sample was 18 inpatient at mental hospital, Lampung Indonesia. By criteria who has a experience of violent behavior.Results: The average score of (pre-treatment) a cognitive behavioral group therapy program in stimulation of perception of 7.94 (SD± 2.838) (post-treatment) of 10.50 ( SD±2.203). The test results obtained p-value = 0,000, therefore, there is a significant effectiveness of a cognitive behavioral group therapy program for reducing violence risk in persons with schizophrenia.Conclusion: The evident a significant effectiveness of a cognitive behavioral group therapy program for reducing violence risk in persons with schizophrenia. Suggestions to hospital management to be regularly to apply that therapy as an effort to help clients in control of their violent behavior.